Physicochemical Characterization of Different Citrus varieties Grown Under Semi-Arid Conditions of Bundelkhand Region - Anjana Kholia; Ghyanshyam Abrol; Ranjit Pal; Suraj.S.H. (Annals of Arid Zone, 2024)
This study evaluated the physical and biochemical characteristics of different citrus cultivars grown under semi-arid conditions in the Bundelkhand region of India. The study included four sweet orange, four mandarin, and four acid lime cultivars. The results showed significant variations in fruit quality among the different varieties, with some showing promising traits such as high juice content, acidity, and vitamin C levels. The study found that sweet orange variety Pusa Round had the highest fruit weight, length, and width, while mandarin variety Daisy had the highest juice content and acid lime variety Pusa Udit had the highest vitamin C content. The study also found significant differences in biochemical parameters such as titratable acidity, total sugars, and ascorbic acid content among the different citrus cultivars. The findings of this study have important implications for citrus cultivation and breeding in the region, suggesting that specific cultivars may be better suited to local agro-climatic conditions.